2007
DOI: 10.1074/jbc.m603822200
|View full text |Cite
|
Sign up to set email alerts
|

Human SSRP1 Has Spt16-dependent and -independent Roles in Gene Transcription

Abstract: The facilitating chromatin transcription (FACT) complex, a heterodimer of SSRP1 and Spt16, has been shown to regulate transcription elongation through a chromatin template in vitro and on specific genes in cells. However, its global role in transcription regulation in human cells remains largely elusive. We conducted spotted microarray analyses using arrays harboring 8308 human genes to assess the gene expression profile after knocking down SSRP1 or Spt16 levels in human non-small cell lung carcinoma (H1299) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 50 publications
5
57
0
Order By: Relevance
“…Consistently, in mammals, SSRP1 has additional, SPT16-independent roles in RNAPII transcription (Antosch et al, 2012). Thus, SSRP1 can act as a coactivator of sequence-specific transcription factors (Spencer et al, 1999;Zeng et al, 2002), and transcript profiling revealed SSRP1-specific targets (Li et al, 2007). Moreover, Arabidopsis SSRP1, but not SPT16, is required for the action of the DNA demethylase DME in the central cell of the female gametophyte (Ikeda et al, 2011).…”
Section: Discussionmentioning
confidence: 71%
“…Consistently, in mammals, SSRP1 has additional, SPT16-independent roles in RNAPII transcription (Antosch et al, 2012). Thus, SSRP1 can act as a coactivator of sequence-specific transcription factors (Spencer et al, 1999;Zeng et al, 2002), and transcript profiling revealed SSRP1-specific targets (Li et al, 2007). Moreover, Arabidopsis SSRP1, but not SPT16, is required for the action of the DNA demethylase DME in the central cell of the female gametophyte (Ikeda et al, 2011).…”
Section: Discussionmentioning
confidence: 71%
“…The first study analyzed global gene expression profiles in lung adenocarcinoma cells upon inhibition of either SSRP1 or SPT16 expression using shRNA, and found that there is a set of genes that are differentially dependent on either SSRP1 or SPT16 expression. 12 The second paper demonstrated that SSRP1, but not SPT16, is involved in regulating spindle formation during mitosis. 28 It should be noted, however, that neither of these studies unequivocally established that FACT subunits act independently.…”
Section: Discussionmentioning
confidence: 99%
“…11, 12 Despite these intriguing functions (and the possibility of additional functions that have yet to be described), FACT has been primarily studied in single cell models, such as yeast and cultured human tumor cells, and the physiological roles of FACT in multicellular organisms remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, Spt16-depleted yeast exhibits a G 1 phase delay, pointing to specific functions of either FACT component (MorilloHuesca et al, 2010). Similarly, human SSRP1 and SPT16 (SUPT16H) can regulate largely overlapping, but also distinct targets (Li et al, 2007).…”
Section: Ssrp1a Promotes Cell Cycle Progression In the Digestive Systmentioning
confidence: 99%